The Concept of Fairness as Expressed in Javanese Propositions: A Study of Cultural Wisdom - Rahyono, F. X. (Makara Human Behavior Studies in Asia, 2011)
One of the Javanese’s highest cultures is the creation of cultural wisdom that conveys the concept of fairness as expressed in propositions as well as cultural expressions. This research aims to revive the memories of Javanese cultural wisdom especially those related to fairness. Based on the propositions, the objective of this research is to identify the concept of fairness behavior in Javanese culture. This research is qualitative. The data were collected from text books and literary texts validated by in-depth interviews as well as forum group discussions. The data corpuses were analyzed by using componential and taxonomic analysis. Through semantic and pragmatic analysis, the fairness concept in Javanese culture can be identified. Bisa ngrumangsani is the main principle of fairness in Javanese propositions and covers two sub-ordinates propositions, i.e. self-restraint and appreciation for others. Each of these two sub-ordinate propositions covers four sub-ordinate propositions referring to action, character, desire, and competence. All of these propositions are sustained by the other proposition creating a whole concept of fairness. The results of this research are expected to serve as groundwork on how the education of national character building relating to fairness behavior can be realized.